PENGARUH PERUBAHAN POSISI TERHADAP POLA NAFAS PADA PASIEN GANGGUAN PERNAFASAN - Rizky Annisa; Wasisto Utomo; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Low fowler, semi fowler and standart fowler position have a related or reducing shortness of breath. The purpose ofthis study was to determine the effect of position changes on respiratory pattern for respiratory disorders of patients inone of the hospitals in Riau Province by using the design of quantitative research and design of quasy experiments forcorrelation mechanism. The sample of this research is 17 respondents based on inclusion criteria using non probabilitysampling technique. The method used in research are quastionnare, obsevation and SOP at low, semi and standartposition. The analisis used univariate analysis to know the frequency distribution and bivariat using cochran test andrepeated anova. The result of this research showed that 17 respondent’s with gender frequency of women were 9respondents(52,9%), frequency of elder >45 year old were 13 responden (76,9%), frequency of elementry schooleducation were 9 responden (52,9%) andterm of care that less than a week were 15 responden (88,2%). The result ofstatistik test p valeu > α (0,05), it showed the effect of changing position on respiratory pattern for patient’s respiratorydisorder of patients in one of the hospitals in Riau Province.Keyword: Position, respiratory, resporatory disorders